The paradox of cultural heritage: Arequipan perspectives between identity safeguarding and the demands of economic growth - Aranibar Ramos, Edgar Romario (2026)
Cultural heritage is a strategic resource for identity construction and socio-economic development. However, its management faces a structural tension between preserving authenticity and responding to the pressures of economic growth. This study addresses this paradox from a Global South perspective, where the dynamics of globalization and structural inequalities intensify the debate. The research addresses how to reconcile identity safeguarding with the opportunities and risks associated with economic development. A qualitative exploratory approach was adopted, employing structured interviews with 31 stakeholders connected to the Historic Centre of Arequipa, Peru, a UNESCO World Heritage Site. Thematic analysis, supported by specialised software, revealed divergent perceptions of authenticity, highlighted the ambivalent impact of cultural tourism, and underscored the potential of participatory strategies, advanced technologies, and multisectoral governance to mitigate risks. The study helps fill a gap in the literature by integrating preservation and adaptive conservation approaches within a single analytical framework. Findings guide for more inclusive and sustainable heritage policies that balance identity with economic growth.